2019
DOI: 10.1126/science.aav0177
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of methane: A selective industrial route to methanesulfonic acid

Abstract: Direct methane functionalization to value-added products remains a challenge because of the propensity for overoxidation in many reaction environments. Sulfonation has emerged as an attractive approach for achieving the necessary selectivity. Here, we report a practical process for the production of methanesulfonic acid (MSA) from only two reactants: methane and sulfur trioxide. We have achieved >99% selectivity and yield of MSA. The electrophilic initiator based on a sulfonyl peroxide derivative is protona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 26 publications
5
54
0
Order By: Relevance
“…For single atoms, δ = 100%. For NPs, δ was calculated using the following equations (equations [11][12][13] given by Vannice 29 :…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For single atoms, δ = 100%. For NPs, δ was calculated using the following equations (equations [11][12][13] given by Vannice 29 :…”
Section: Methodsmentioning
confidence: 99%
“…For instance, aqueous Au-Pd colloids achieved selective oxidation of methane into methanol with H 2 O 2 as an oxidant under 30 bar of CH 4 at 50°C 10 . Methane was reported to be oxidized into methanesulfonic acid by SO 3 over an electrophilic initiator at 50°C 11 . However, these processes generally involve corrosive oxidant or expensive media, such as H 2 O 2 , oleum, trifluoroacetic acid, and hydrobromic acid, which is not suitable for commercialization [12][13][14][15] .…”
mentioning
confidence: 99%
“…Fundamentally, this catalytic conversion requires low activation energy and high reactivity, in order to accommodate the low thermal energy and partial pressure of CH 4 substrate at ambient condition. Existing approaches of CH 4 functionalization usually operated at high pressure and/or elevated temperature [3][4][5][6][7][8][9][10][11][12][13][14][15][16] , involve metal-catalyzed reactions [3][4][5][6][7] , superacid-based activation 17 , or catalysis based on peroxo species for a free-radical chain mechanism [8][9][10] . For the metal-catalyzed reactions reported by Periana and others ( Fig.…”
mentioning
confidence: 99%
“…[6] Later, Bell et al reported direct conversion of methane to methanesulfonic acid. [7] Recently, Díaz-Urrutia and Ott reported a practical process for the production of methanesulfonic acid from methane and sulfur trioxide, [8] promising in industrial application. On the other hand, however, the associated fundamental research -for example the gas-phase study on methane activation with CÀ S coupling -is lacking.…”
mentioning
confidence: 99%